Collaborative Governance Regimes - Emerson, Kirk; Nabatchi, Tina (Book collections on Project MUSE., 2015)
Collaboration among public agencies, across different governmental levels, and/or with the private and civic sectors and the public is increasingly called on to handle the complex, multi-jurisdictional challenges we face in the 21st century. Experiments in collaborative public management, multi-partner governance, joined-up or network government, hybrid sectoral arrangements, co-management regimes, participatory governance, and civic engagement have evolved, and in some cases, transformed the way the public's business is getting done. The growth of these innovative collaborative governance systems has outpaced scholarship. While the academic literature has spawned numerous case studies and context- or policy-specific models for collaboration, there have been few efforts to integrate extant knowledge into a framework that is broadly applicable for both research and practice and across sectors, settings, and scales. This book seeks to fill that gap.